Spiro N‐methoxy piperidine ring containing aryldiones for the control of sucking insects and mites: discovery of spiropidion. Issue 10 (6th February 2020) - Muehlebach, Michel; Buchholz, Anke; Zambach, Werner; Schaetzer, Juergen; Daniels, Miriam; Hueter, Ottmar; Kloer, Daniel P; Lind, Rob; Maienfisch, Peter; Pierce, Andy; Pitterna, Thomas; Smejkal, Tomas; et al.
Abstract: BACKGROUND: Crop protection solutions for the control of key economic sucking pests derive essentially from neuronal and muscular acting chemistries, wherein neonicotinoid uses largely dominated for the last two decades. Anticipating likely resistance development of some of those arthropod species to this particular class, we intensified research activities on a non‐neuronal site of action targeting insect growth and development some 10 years ago. RESULTS: Our innovation path featured reactivation of a scarcely used and simple building block from the 1960s, namely N ‐methoxy‐4‐piperidone 3. Its judicious incorporation into the 2‐aryl‐1, 3‐dione scaffold of IRAC group 23 inhibitors of fatty acid biosynthesis resulted in novel tetramic acid derivatives acting on acetyl‐coenzyme A carboxylase (ACCase). The optimization campaign focused on modulation of the aryl substitution pattern and understanding substituent options at the lactam nitrogen position of those spiroheterocyclic pyrrolidine‐dione derivatives towards an effective control of sucking insects and mites. This work gratifyingly culminated in the discovery of spiro N ‐methoxy piperidine containing proinsecticide spiropidion 1. Following in planta release, its insecticidally active dione metabolite 2 is translaminar and two‐way systemic (both xylem and phloem mobile) for a full plant protection against arthropod pests. CONCLUSION: Owing to such unique plant systemic properties, growing shoots and roots actually not directly exposed to spiropidion‐based chemistry after foliar application nevertheless benefit from its long‐lasting efficacy. Spiropidion is for use in field crops, speciality crops and vegetables controlling a broad range of sucking pests. In light of other performance and safety profiles of spiropidion, an IPM fit may be expected. © 2020 Society of Chemical Industry Abstract : Owing to good translaminar distribution and both xylem and phloem mobility (two‐way systemicity) in crops, full plant circulated spiropidion‐based chemistry effectively controls sucking pests with different cellular feeding sites.